2014
DOI: 10.1038/ncomms6383
|View full text |Cite
|
Sign up to set email alerts
|

The oestrogen receptor alpha-regulated lncRNA NEAT1 is a critical modulator of prostate cancer

Abstract: The androgen receptor (AR) plays a central role in establishing an oncogenic cascade that drives prostate cancer progression. Some prostate cancers escape androgen dependence and are often associated with aggressive phenotype. The estrogen receptor alpha (ERα) is expressed in prostate cancers, independent of AR status. However, the role of ERα remains elusive. Using a combination of chromatin immunoprecipitation (ChIP) and RNA-sequencing data, we identified an ERα specific non coding transcriptome signature. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
464
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 550 publications
(482 citation statements)
references
References 51 publications
16
464
1
1
Order By: Relevance
“…During the differentiation of embryonic stem cells and muscle cells, NEAT1 lncRNAs have been found to be upregulated (14,16). A previous study reported that estrogen receptor α-regulated NEAT1 lncRNA acted as a transcriptional regulator and promoted tumorigenesis leading to prostate adenocarcinoma in experimental animal models (34). Furthermore, NEAT1 expression was associated with oncogenic activity and metastatic progression in lung cancer (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…During the differentiation of embryonic stem cells and muscle cells, NEAT1 lncRNAs have been found to be upregulated (14,16). A previous study reported that estrogen receptor α-regulated NEAT1 lncRNA acted as a transcriptional regulator and promoted tumorigenesis leading to prostate adenocarcinoma in experimental animal models (34). Furthermore, NEAT1 expression was associated with oncogenic activity and metastatic progression in lung cancer (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear receptors recruit multiple enzymatically diverse epigenetic coregulators, including p160/p300 lysine acetyltransferase, demethylases that cooperate with the mediator complex to stabilize recruitment of the basal transcriptional machinery, and RNA polymerase II. (B) Evidence from genome-wide chromatin immunoprecipitation studies indicate the recruitment of AR in LNCaP, 22Rv1, VCaP PCa cells (GSM698597) (Sharma et al 2013), and ERa in VCaP (GSM1076110) (Chakravarty et al 2014) to the VEGF promoter.…”
Section: Transcriptional Regulation Of Pro-angiogenesis Pathways In Pcamentioning
confidence: 99%
“…MALAT1 expression was higher in thyroid cancer tissues and in thyroid cancer cells than normal thyroid (Huang, et al 2016a). Likewise, NEAT1 upregulated in breast , endometrial ); ovarian ) and thyroid tumors , and is the highest lncRNA in prostate cancer and strongly associated with metastasis (Chakravarty, et al 2014). …”
Section: Examples Of Lncrnas Dysregulated In Endocrine-related Cancersmentioning
confidence: 99%